1999
DOI: 10.3758/bf03200738
|View full text |Cite
|
Sign up to set email alerts
|

Concreteness, context availability, and imageability ratings and word associations for abstract, concrete, and emotion words

Abstract: Normative values on various word characteristics were obtained for abstract, concrete, and emotion words in order to facilitate research on concreteness effects and on the similarities and differences among the three word types. A sample of 78 participants rated abstract, concrete, and emotion words on concreteness, context availability,and imagery scales, Wordassociations were also gathered for abstract, concrete, and emotion words. The data were used to investigate similarities and differences among these th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
204
2
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(242 citation statements)
references
References 24 publications
33
204
2
3
Order By: Relevance
“…There have been a number of word databases providing information on variables such as imageability, concreteness, or word associations (e.g., Altarriba, Bauer, & Benvenuto, 1999 Table 1 contains a summary of the statistics of the variables contained in the BAWL-R. Figure 1 depicts the quadratic function relating emotional arousal and emotional valence in the affective space.…”
Section: Description Of the Databasementioning
confidence: 99%
“…There have been a number of word databases providing information on variables such as imageability, concreteness, or word associations (e.g., Altarriba, Bauer, & Benvenuto, 1999 Table 1 contains a summary of the statistics of the variables contained in the BAWL-R. Figure 1 depicts the quadratic function relating emotional arousal and emotional valence in the affective space.…”
Section: Description Of the Databasementioning
confidence: 99%
“…A very important step in this line of inquiries was the question about the status of emotion words in the mental lexicon. Altarriba et al (1999) conducted a normative study about the nature of emotion words. They used a word rating task and found that emotion words were between abstract and concrete words regarding imageability and the lowest of the three categories on concreteness and context availability measures.…”
Section: Introductionmentioning
confidence: 99%
“…A lexical database is an organised resource capturing the range of inherent (psycho) linguistic properties of words in a certain language. Lexical databases have been established in some languages, most often English, for which databases exist on imageability, frequency, concreteness, familiarity, meaningfulness and age of acquisition (Paivio, Yuille & Madigan, 1968;Coltheart, 1981;Altarriba, Bauer and Benvenuto, 1999;Balota, Pilotti & Cortese 2001;Bird, Franklin & Howard 2001;Cortese & Khanna, 2008;Brysbaert, Warriner & Kuperman, 2014). Similar lexical data are also available for several other languages, such as Swedish (Blomberg & Öberg, 2015), Norwegian , Portuguese (Marques et al, 2007), Italian (Rofes, de Aguiar & Miceli, 2015), Dutch (Ghyselinck, De Moor & Brysbaert, 2000), and French (Flieller & Tournois, 1994).…”
Section: Introductionmentioning
confidence: 99%